TIPE2 negatively regulates inflammation by switching arginine metabolism from nitric oxide synthase to arginase. - Yunwei Lou; Guizhong Zhang; Minghong Geng; Wenqian Zhang; Jian Cui; Suxia Liu (PLoS ONE, 2014)
TIPE2, the tumor necrosis factor (TNF)-alpha-induced protein 8-like 2 (TNFAIP8L2), plays an essential role in maintaining immune homeostasis. It is highly expressed in macrophages and negatively regulates inflammation through inhibiting Toll-like receptor signaling. In this paper, we utilized RAW264.7 cells stably transfected with a TIPE2 expression plasmid, as well as TIPE2-deficient macrophages to study the roles of TIPE2 in LPS-induced nitric oxide (NO) and urea production. The results showed that TIPE2-deficiency significantly upregulated the levels of iNOS expression and NO production in LPS-stimulated macrophages, but decreased mRNA levels of arginase I and urea production. However, TIPE2 overexpression in macrophages was capable of downregulating protein levels of LPS-induced iNOS and NO, but generated greater levels of arginase I and urea production. Furthermore, TIPE2-/- mice had higher iNOS protein levels in lung and liver and higher plasma NO concentrations, but lower levels of liver arginase I compared to LPS-treated WT controls. Interestingly, significant increases in IκB degradation and phosphorylation of JNK, p38, and IκB were observed in TIPE2-deficient macrophages following LPS challenge. These results strongly suggest that TIPE2 plays an important role in shifting L-arginase metabolism from production of NO to urea, during host inflammatory response.